PENGEMBANGAN BEE POLLEN SNACK BAR UNTUK ANAK USIA SEKOLAH - Qurratu Aini; Ahmad Sulaeman; Tiurma Sinaga (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2020)
The objective of this study was to analyze the nutrition content, antioxidant activity, mineral bio-availability and amino acid composition of a bee pollen snack bar. This study was a pure experimental study along with complete randomized design. The treatment factor was the addition of bee pollen which resulted in five formulas. The product was made from Sormeal, rice crispy, chocolates, dates, cashews and bee pollen. Formula F3 with the addition of bee pollen of 10% was analyzed for its nutrient content, antioxidant activity and availability of Fe and Zn. The F3 formula contained 5.91% water, 1.72% ash, 11.30% protein, 16.52% fat and 64.52 carbohydrate. The antioxidant activity test of the product was 10.77 mg ascorbic acid/g sample. Meanwhile, the bioavalaibility of Fe and Zn of the product were 17.02 and 6.84 mg/kg, respectively. This product can be considered as a nutritious snack that could improve imunity and potentially improve school-aged children learning performance.